HUBUNGAN TEKNIK MENYIKAT GIGI DENGAN GINGIVITIS PADA IBU-IBU PEDAGANG DI PASAR TRADISIONAL RINTE MEDAN - Simaremare, Susy Adrianelly; Ngena Ria; Nelly K Manurung (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
The success of maintaining dental health depends on daily brushing techniques. Improper toothbrushing technique can cause gingival inflammation, namely gingivitis. This study was conducted to analyze correlation between tooth brushing technique with the occurrence of gingivitis on seller women at traditional market in Medan. Correlative descriptive research design with cross sectional design. The population of this study were all seller women at Rinte Traditional Market in Medan with total sample of 35 respondent’s taken by total sampling technique. Data collection tool for the accuracy of brushing technic variables used a interviews using checklist interview guidelines, while gingivitis data was measured by examining gingival condition. According to the Chi-Square test, the p value was 0.000<? (?=0.005), meaning that there was Corelation between Tooth Brushing Technique with gingivitis.